PENGARUH KOMPENSASI DAN DISPLIN KERJA TERHADAP KINERJA NON PNS PADA KANTOR KECAMATAN SETU KOTA TANGERANG SELATAN - Salsabila, Zahrani; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of compensation and work discipline on the performance of non-civil servants at the Setu sub-district office, South Tangerang city, both partially and simultaneously. The method used is associative quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 60 respondents. Data analysis uses validity tests, reality tests, classical assumption tests, quantitative analysis, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. Based on the results of this research, compensation has a significant effect on employee performance with a coefficient of determination value of 68.1% and the hypothesis test obtained a calculated t value > t table or (11.133 > 2.002). Work discipline has a significant effect on employee performance with a coefficient of determination value of 85.5% and the hypothesis test obtained a calculated t value > t table or (18.506 > 2.002). Compensation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 1.687 + 0.167X1 + 0.794X2. The simultaneous determination coefficient value is 86.5% while the remaining 13.5% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (182.232 > 3.160).